Sexual Violence, Title IX and Women's College Enrollment - Dave E. Marcotte; Jane E. Palmer (Institute for the Study of Labor (IZA), 2016)
Sexual violence has long been a problem on college campuses, yet federal policies to protect students have largely been ineffectual. Spurred by student grievances, the U.S. Department of Education's Office of Civil Rights recently began investigating how sexual assault cases were handled at a number of institutions under the Title IX provisions of the Education Amendments of 1972. These investigations focus attention on specific colleges' responses to cases of sexual violence and raise the specter that these institutions may fail to properly investigate allegations or punish perpetrators. In this paper, we examine the implications of these investigations on college enrollment, particularly for women. We combine institution-level panel data on enrollment by age and gender, with information on Title IX investigations to study changes in women's college enrollment. We estimate that enrollment of women at colleges under Title IX investigation declined by 16 to 22 percent. The declines are consistent with both declining matriculation and retention of female students.
Keywords: I24; J16; 330; college; educational attainment; sexual assault